Systemic sclerosis and the gastrointestinal tract - Irena Walecka (Gastroenterology Review)
Systemic sclerosis (SSc) is an autoimmunological disease of unknown origin with complex pathogenesis and multiple organ involvement. It is characterised by vascular and immunological abnormalities leading to fibrosis of the skin and internal organs. It is a rather rare disease with a prevalence of around 20 per 100,000. The disease results in heterogeneous clinical findings and different courses. Systemic sclerosis usually begins with the onset of Raynaud’s phenomenon (RP), followed by skin sclerosis and internal organ involvement, although it may appear synchronously with RP. Gastrointestinal involvement is a serious and prevalent complication of SSc, and the oesophagus is the most frequently affected organ. Both limited and diffuse cutaneous SSc involve internal organs, with the involvement of the gastrointestinal tract as a leading cause of morbidity. At present, treatment is mainly symptomatic with no disease-modifying drugs.